2022
DOI: 10.1007/s10853-022-06990-7
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on the effects of process-induced porosity on the mechanical properties of alloys fabricated by laser powder bed fusion

Abstract: Laser powder bed fusion (LPBF) is an emerging additive manufacturing technique that is currently adopted by a number of industries for its ability to directly fabricate complex near-net-shaped components with minimal material wastage. Two major limitations of LPBF, however, are that the process inherently produces components containing some amount of porosity and that fabricated components tend to suffer from poor repeatability. While recent advances have allowed the porosity level to be reduced to a minimum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(30 citation statements)
references
References 241 publications
(306 reference statements)
0
30
0
Order By: Relevance
“…As a result, these outcomes are hardly amenable to systematization and classification. Moreover, the complexity of technologies tends increase in order to meet the main challenges of additive manufacturing: porosity due to powder materials use [ 74 ], residual stresses due to significant heating and cooling rates [ 75 ], the requirements for surface roughness [ 76 ] and tailoring the operational properties for different applications (namely bearing [ 77 ], magnetic [ 78 ], biomedical [ 79 , 80 ], refractory [ 19 ], etc.). At present, there are about 30 different metal additive manufacturing (MAM) processes.…”
Section: Classification Of the Mam Processes Used For Ti 2 ...mentioning
confidence: 99%
“…As a result, these outcomes are hardly amenable to systematization and classification. Moreover, the complexity of technologies tends increase in order to meet the main challenges of additive manufacturing: porosity due to powder materials use [ 74 ], residual stresses due to significant heating and cooling rates [ 75 ], the requirements for surface roughness [ 76 ] and tailoring the operational properties for different applications (namely bearing [ 77 ], magnetic [ 78 ], biomedical [ 79 , 80 ], refractory [ 19 ], etc.). At present, there are about 30 different metal additive manufacturing (MAM) processes.…”
Section: Classification Of the Mam Processes Used For Ti 2 ...mentioning
confidence: 99%
“…As a result, the specimens produced by LPBF show a lower fatigue strength than conventionally produced material, which is a well-known phenomenon in many studies. [5,7,11,13,27] Eliminating the porous defects in the material is crucial to improve the fatigue strength of the components produced by LPBF. HIP with integrated heat treatment can modify the microstructure and densify the material simultaneously.…”
Section: Fatigue Tests and Failure Analysismentioning
confidence: 99%
“…The relationship between porosity and mechanical properties was also studied by various researchers. They found that the porosity degrades the mechanical properties [12], [13] and, thus, limits the lifetime of a product [20].…”
Section: Introductionmentioning
confidence: 99%